2022
DOI: 10.1001/jama.2022.17714
|View full text |Cite
|
Sign up to set email alerts
|

Association of Extracorporeal Membrane Oxygenation With New Mental Health Diagnoses in Adult Survivors of Critical Illness

Abstract: ImportanceExtracorporeal membrane oxygenation (ECMO) is used as temporary cardiorespiratory support in critically ill patients, but little is known regarding long-term psychiatric sequelae among survivors after ECMO.ObjectiveTo investigate the association between ECMO survivorship and postdischarge mental health diagnoses among adult survivors of critical illness.Design, Setting, and ParticipantsPopulation-based retrospective cohort study in Ontario, Canada, from April 1, 2010, through March 31, 2020. Adult pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 35 publications
0
27
1
Order By: Relevance
“…In Reply Our study demonstrated a modest association between survivorship after ECMO and new mental health diagnoses. In their Letter, Drs Li and Li hypothesize that this association may have been mediated by differences in sedation among patients exposed to ECMO.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…In Reply Our study demonstrated a modest association between survivorship after ECMO and new mental health diagnoses. In their Letter, Drs Li and Li hypothesize that this association may have been mediated by differences in sedation among patients exposed to ECMO.…”
mentioning
confidence: 61%
“…A recent study demonstrated that patients who survive after receiving ECMO support experience substantial physical disability in the 6 months after discharge, regardless of baseline level of function . Because physical function is so closely tied to mental health morbidity, it stands to reason that this may contribute to the potential causes for the association we have demonstrated in our study . Future research using more granular data is necessary to elucidate the potential mechanisms that underlie this association.…”
mentioning
confidence: 64%
“…To the Editor A recent study found that extracorporeal membrane oxygenation (ECMO) was significantly associated with a modestly increased risk of new mental health diagnoses or social problems in adult survivors of critical illness in Canada. Although Cox regression analyses were performed to determine the independent factors associated with new mental health diagnoses or social problems, it is important to consider the role of sedation in patients treated with ECMO.…”
mentioning
confidence: 99%
“…Surviving ECMO treatment was significantly associated with an increased risk of new mental problems. 7 As a result of the study design, it is only possible to hypothesize about the causal factors between ECMO and new mental health problems. The authors elaborate about biological mechanisms that may manifest in psychiatric morbidity.…”
mentioning
confidence: 99%
“…The authors underscore that future studies should elucidate the potential mechanisms underlying these relationships. 7 In the study by Fernando et al, 7 only preexisting mental health diagnosis (HR, 2.39 [95% CI, 1.78-3.20]) and having had an outpatient psychiatry visit in the year prior to the index admission (HR, 1.82 [95% CI, 1.25-2.65]) were significantly associated with outcome of a new mental health diagnosis. This finding corroborates results of previous studies that showed pre-ICU health status was the most important prognostic factor for mental health outcomes after ICU care, and even suicide.…”
mentioning
confidence: 99%